Investment portfolio optimization using evolutionary strategies - Li, Chenchen. (2013)
Talking about investment, people may simply think to put money in a saving account in a bank. However, such small amount earned by bank interest cannot keep ahead with the growing inflation rate and the value of the money is depreciated. Therefore, more and more people are interested in putting a portion of their savings in more aggressive investments, such as stock, which can offer a handsome return that wins inflation and create more wealth.